Praktek Pengolahan Buah Nanas Menjadi Selai Nanas Sebagai Peluang Bisnis di Desa Duriaasi - Endang Sumiratin; Made Sukratman; Mursal Junus (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2024)
The purpose of this PKM is to carry out the practice of processing pineapple fruit into pineapple jam for the women of Rt 01 Hamlet 1 in Duriaasi Village, Wonggeduku District. The PKM activity was held at the house of the Chairwoman of Rt 01 Dusun 1 Duriaasi Village on Saturday, November 9, 2024. The training activity on processing pineapples into nana jam in Hamlet 1 of Duriasi Village has been running well. This activity also received a positive response from Rt 01 women who were participants and were able to make a good contribution. The Rt 01 women who took part in the training have been able to process pineapples into pineapple jam products without preservatives. This training is expected to open up business opportunities for the community. The community also wants similar activities to be held again periodically with different types of processed products.